Profil Senyawa Bioaktif Ekstrak Kalus Biji Jeruk Purut (Citrus hystrix DC.) Pasca Induksi Metil Jasmonat - Yeni Avidhatul Husnah; Ari Indrianto; Woro A.S Tunjung (Biotropic : The Journal of Tropical Biology, 2019)
Kaffir lime (Citrus hystrix DC.) is an alternative source of potential and relatively safe anticancer compounds as it contains bioactive components. Previous study has shown that the extract of kaffir lime leaves contains terpenoids and potentially as anticancer. However, the content of bioactive compounds may vary due to environmental factors. Callus culture is an alternative method of induction of bioactive compound content with a controlled environment. Previous study has succeeded in inducing callus from kaffir lime seed explants produce the ideal callus with a crumb / friable texture. Methyl jasmonate is reported to induce the production of secondary metabolite compounds. Elicitation with methyl jasmonate is one of the strategy to increase terpenoids from cultured cells Objective of this study is anlyze the using of methyl jasmonate as elicitor.to increase bioactive compounds inkaffir lime cell suspension. Callus induced from seed explants age 40 days were transferred into liquid medium for the initiation of suspension culture. Subculture is done when the age of culture reaches 21 days then measured thegrowth curve o f cell supension and concentration of sucrose in medium. After cells reached log phse in 12 days then be treated with methyl jasmonic for 8 days. The cell suspension then beextracted with ethyl acetate by maceration method. The content of bioactive compounds in the extract was anlyzed with GC-MS. Suspension of lime lime cells C. hystrix, without treatment yields fatty acid compounds. Bioactive compounds produced by suspended cell suspension after methyl jasmonate elicitation is germacrene A, myrcene, alpha-terpineol, geranyl acetate, trans-caryophyllene, delta-guaiene and several types of ester fatty acids.